The status of Bayan Al-Haq Mahmud Al-Nisabauri (After 505 AH) in his book (Baher Al-Burhan fi Ma’ani Mushkilat Al-Quran) among scholars of the problem of the Holy Quran - Al-Mashaqba, Fadi Ahmad (Journal of Arabic Language Sciences and Literature, 2022)
This study aims to demonstrate the status of Bayan al-Haqq al-Nisaburi in his book Bahir al-Burhan in the meanings of the problems of the Quran compared with some scholars of the problem of the Quran namely Ibn Qutayba in his book Taweel al –Mushkal al-Quran Makki in his book The Proplem of Paraphrasing the Quran and al-Kirmani in his book Secrets of Repetition in the Quran and this comparision relates to the similarities And the difference in terms of their methodology and references in their grammatical morphological and linguistic directives to the problematic Quranic verses and l mentioned this citting the Quran verses that clarify this.